DIGITAL ECONOMY – AN ELEMENT OF INFORMATION - Georgieva, E. A.; Аkimbaeva, К. Т.; Askarova, Zh. A.; Kyzdarbekova, A. S. (Farabi Journal of Social Sciences, 2020)
Over the past decades, the world has been rapidly moving towards a new type of economy, where digital technologies are becoming the main tool for its formation. Expanding the role of information technology in the private and public sectors is the basis for the transition to a digital state. The term «digital economy» (digitaleconomy) was first used relatively recently, in 1995, by an American scientist from the University of Massachusetts, Nicholas Negroponte, to explain to colleagues the advantages of the new economy in comparison with the old one in connection with the intensive development of information and communication technologies. The article deals with the concept of the digital economy, its introduction, and the world experience of structural and institutional support for the development of the digital economy. Special attention is paid to the development and implementation of digital technologies in the economy. Based on the studied material, it was concluded that for the application of modern technologies in all sectors of human life, it is necessary to develop appropriate programs that ensure the effective use of digital technologies.